Sexual dimorphic response to rituximab treatment: A longitudinal observational study in a large cohort of patients with primary membranous nephropathy and persistent nephrotic syndrome - Perna, Annalisa; Ruggiero, Barbara; Podestà, Manuel Alfredo; Perico, Luca; Orisio, Silvia; Debiec, Hanna; Remuzzi, Giuseppe; Ruggenenti, Piero (Frontiers in Pharmacology, 2022)
Rituximab is one of the first-line therapies for patients with membranous nephropathy (MN) at high risk of progression towards kidney failure. We investigated whether the response to Rituximab was affected by sex and anti-PLA2R antibody levels in 204 consecutive patients (148 males and 56 females) with biopsy-proven MN who were referred to the Nephrology Unit of the Azienda Socio Sanitaria Territoriale Papa Giovanni XXIII from March 2001 to October 2016 and managed conservatively for at least 6 months. The primary outcome was a combined endpoint of complete (proteinuria <0.3 g/24 h) or partial (proteinuria <3.0 g/24 h and >50% reduction vs. baseline) remission. Patients gave written informed consent to Rituximab treatment. The study was internally funded. No pharmaceutical company was involved. Anti-PLA2R antibodies were detectable in 125 patients (61.3%). At multivariable analyses, female gender (p = 0.0198) and lower serum creatinine levels (p = 0.0108) emerged as independent predictors of better outcome (p = 0.0198). The predictive value of proteinuria (p = 0.054) and anti-PLA2R titer (p = 0.0766) was borderline significant. Over a median (IQR) of 24.8 (12.0–36.0) months, 40 females (71.4%) progressed to the combined endpoint compared with 73 males (49.3%). Anti-PLA2R titers at baseline [127.6 (35.7-310.8) vs. 110.1 (39.9–226.7) RU/ml] and after Rituximab treatment were similar between the sexes. However, the event rate was significantly higher in females than in males [HR (95%): 2.12 (1.44–3.12), p = 0.0001]. Forty-five of the 62 patients (72.3%) with anti-PLA2R titer below the median progressed to the combined endpoint versus 35 of the 63 (55.6%) with higher titer [HR (95%): 1.97 (1.26–3.07), p < 0.0029]. The highest probability of progressing to the combined endpoint was observed in females with anti-PLA2R antibody titer below the median (86.7%), followed by females with anti-PLA2R antibody titer above the median (83.3%), males with titer below the median (68.1%), and males with titer above the median (44.4%). This trend was statistically significant (p = 0.0023). Similar findings were observed for complete remission (proteinuria <0.3 g/24 h) and after analysis adjustments for baseline serum creatinine. Thus, despite similar immunological features, females were more resilient to renal injury following Rituximab therapy. These findings will hopefully open new avenues to identify the molecular pathways underlying sex-related nephroprotective effects.